2014
DOI: 10.1136/jnnp-2014-308826
|View full text |Cite
|
Sign up to set email alerts
|

CMT subtypes and disease burden in patients enrolled in the Inherited Neuropathies Consortium natural history study: a cross-sectional analysis

Abstract: BackgroundThe international Inherited Neuropathy Consortium (INC) was created with the goal of obtaining much needed natural history data for patients with Charcot-Marie-Tooth (CMT) disease. We analysed clinical and genetic data from patients in the INC to determine the distribution of CMT subtypes and the clinical impairment associated with them.MethodsWe analysed data from 1652 patients evaluated at 13 INC centres. The distribution of CMT subtypes and pathogenic genetic mutations were determined. The disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
306
12
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(346 citation statements)
references
References 30 publications
21
306
12
7
Order By: Relevance
“…[5][6][7][8] One large prospective study indicated that as many as 42% of patients with previously undiagnosed polyneuropathy coming to tertiary care referral had familial occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] One large prospective study indicated that as many as 42% of patients with previously undiagnosed polyneuropathy coming to tertiary care referral had familial occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Charcot Marie Tooth disease type 4J (CMT4J) is a rare inherited peripheral neuropathy, affecting 0.24% of people with CMT,1 caused by biallelic disease causing variants in the FIG4 gene. CMT4J may present either as an early and severe, or a late onset and more slowly progressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly half of these patients have CMT1A,2 a demyelinating neuropathy caused by a 1.4‐Mb duplication in chromosome 17p12 that contains the peripheral myelin protein 22 gene, PMP22 , an integral membrane protein expressed in PNS compact myelin 3, 4. CMT1A is hypothesized to occur as a result of nonallelic homologous recombination (NAHR)5, 6, 7 in a region of 17p12 surrounding and including the PMP22 gene, causing increased expression of the normal gene product.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations within the PMP22 gene are classified as CMT1E 2. Most CMT1E mutations are missense mutations probably resulting in a gain‐of‐new protein function 8.…”
Section: Introductionmentioning
confidence: 99%